Advanced Hybrid GaN/ZnO Nanoarchitectured Microtubes for Fluorescent Micromotors Driven by UV Light. Issue 2 (9th December 2019) - Wolff, Niklas; Ciobanu, Vladimir; Enachi, Mihail; Kamp, Marius; Braniste, Tudor; Duppel, Viola; Shree, Sindu; Raevschi, Simion; Medina‐Sánchez, Mariana; Adelung, Rainer; Schmidt, Oliver G.; Kienle, Lorenz; et al.
Abstract: The development of functional microstructures with designed hierarchical and complex morphologies and large free active surfaces offers new potential for improvement of the pristine microstructures properties by the synergistic combination of microscopic as well as nanoscopic effects. In this contribution, dedicated methods of transmission electron microscopy (TEM) including tomography are used to characterize the complex hierarchically structured hybrid GaN/ZnO:Au microtubes containing a dense nanowire network on their interior. The presence of an epitaxially stabilized and chemically extremely stable ultrathin layer of ZnO on the inner wall of the produced GaN microtubes is evidenced. Gold nanoparticles initially trigger the catalytic growth of solid solution phase (Ga1– x Zn x )(N1– x O x ) nanowires into the interior space of the microtube, which are found to be terminated by AuGa‐alloy nanodots coated in a shell of amorphous GaO x species after the hydride vapor phase epitaxy process. The structural characterization suggests that this hierarchical design of GaN/ZnO microtubes could offer the potential to exhibit improved photocatalytic properties, which are initially demonstrated under UV light irradiation. As a proof of concept, the produced microtubes are used as photocatalytic micromotors in the presence of hydrogen peroxide solution with luminescent properties, which are appealing for future environmental applications and active matter fundamental studies. Abstract : A complex hierarchical design of hybrid GaN/ZnO microtubes functionalized with a dense network of solid solution phase (Ga1– x Zn x )(N1– x O x ) nanowires in the interior of the tube is produced and characterized by a detailed transmission electron microscopy study. The materials photocatalytic activity is demonstrated in context of micromotor application in the presence of hydrogen peroxide solution.